The effect of fuel type on the engine performance of gasoline engine - 280302 Ho, Hock Woo (Skudai : Universiti Teknologi Malaysia, 2000)
Project Paper (Bachelor of Mechanical Engineering (Industrial Mechanical)) - Universiti Teknologi Malaysia, 2000